High-throughput screening campaigns against a PI3Kα isoform bearing the H1047R mutation identified potential inhibitors with novel scaffolds. (November 2018) - Wang, Jia; Gong, Grace; Zhou, Yan; Lee, Woo-Jeong; Buchanan, Christina; Denny, William; Rewcastle, Gordon; Kendall, Jackie; Dickson, James; Flanagan, Jack; Shepherd, Peter; Yang, De-Hua; et al.
Abstract The phosphatidylinositol 3-kinase (PI3K) pathway is involved in many cellular functions including cell growth, metabolism, and transformation. Hyperactivation of this pathway contributes to tumorigenesis, therefore, PI3K is a major target for anticancer drug discovery. Since the PI3Kα isoform is implicated mostly in cancer, we conducted a high-throughput screening (HTS) campaign using a 3-step PI3K homogenous time-resolved fluorescence assay against this isoform bearing the H1047R mutation. A total of 288, 000 synthetic and natural product-derived compounds were screened and of which, we identified 124 initial hits that were further selected by considering the predicted binding mode, relationship to known pan-assay interference compounds and previous descriptions as a lipid kinase inhibitor. A total of 24 compounds were then tested for concentration-dependent responses. These hit compounds provide novel scaffolds that can potentially be optimized to create novel PI3K inhibitors.